Kajian Efisiensi Teknis Perbankan Syariah di Indonesia Periode 2011-2014 - Yudhanto, Septian Fonny; , Didit Purnomo, SE., M.Si; , Dr. Imron Rosyadi, M.Ag (2016)
This research purposed to assessing the technical efficiency of Islamic banking in Indonesia 2011-2014 period seen from the input and output of a Unit of Economic Activity (UKE). The data used in this research is secondary data. Data analysis techniques used in this research is this Data Envelopment Analisys (DEA). Based on data analysis in this study can be concluded from the fifth of islamic banks, that is Bank Syariah Mandiri (BSM), BNI Syariah, BRI Syariah, Bank Mega Syariah, and BCA Syariah. There is only one Islamic bank that is efficient that Bank Mandiri Syariah (BSM), so that there are four islamic banks that goes in the category of inefficiency the average less than one. The four banks that have not been efficient namely, BNI Syariah , BRI Syariah , Bank Mega Syariah , and BCA Syariah.